Table tennis rubber sheet and table tennis racket
A cross-linked silicone rubber sheet with controlled molecular composition addresses the issue of reduced ball speed in silicone rubber sheets by enhancing stress dispersion, maintaining stable performance over repeated hits.
Patent Information
- Application Number
- JP2023120602
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-25
- Publication Date
- 2025-02-06
AI Technical Summary
Existing silicone rubber sheets for table tennis rackets suffer from reduced ball speed when repeatedly hit, leading to unstable ball hit performance over time.
A table tennis rubber sheet composed of cross-linked silicone rubber, decomposed using trimethyl orthoformate, with a specific molecular composition ratio of α and β moles per gram, where α is 1.3 x 10^-5 to 1.0 x 10^-3 mol and β is 9.0 x 10^-6 mol or less, and α/(α+β) is 0.67 to 1.00, enhancing stress dispersion and maintaining flexibility.
The rubber sheet maintains stable ball hit performance by preventing deterioration due to repeated impacts, ensuring consistent speed and rotation without significant loss.
Smart Images

Figure 2025017520000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a table tennis rubber sheet and a table tennis racket. [Background technology]
[0002] Table tennis rackets have a rubber sheet attached to a board called the blade. When the ball is hit, the rubber sheet deforms upon contact with the ball, and the force that returns this deformation to its original shape gives the ball spin and speed.
[0003] In order to increase the amount of spin given to the ball, the more flexible the rubber sheet is and the greater the deformation, the greater the contact area with the ball and the greater the frictional force, which is advantageous. On the other hand, if a rubber sheet is simply used in a soft manner, the speed at which it recovers from deformation may be slower, which may result in a decrease in the speed of the ball. In order to achieve both the amount of spin and the speed of the ball, it is necessary for the rubber sheet to have both flexibility and deformation recovery.
[0004] From the viewpoint of material design of the rubber sheet, the viscoelasticity of the rubber sheet is important in order to further improve the hitting performance such as the amount of spin and the ball speed. Patent Document 1 shows that a rubber sheet with excellent hitting performance can be obtained by setting the Young's modulus E' to 0.01 MPa or more and 1 MPa or less and the loss tangent tanδ to 0.03 or less. In addition, silicone rubber, butadiene rubber, and natural rubber are shown as materials preferable for satisfying such viscoelasticity. In addition, Patent Document 2 shows that a rubber sheet made of silicone rubber can suppress the change in viscoelasticity due to temperature. By using such a rubber sheet, stable hitting performance can be achieved even if the temperature of the game venue changes, for example. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2011-056004 A [Patent Document 2] JP 2011-056005 A Summary of the Invention [Problem to be solved by the invention]
[0006] However, according to the studies of the present inventors, the silicone rubber sheets described in Patent Documents 1 and 2 sometimes result in a decrease in ball speed as a hitting performance when hit repeatedly. At least one aspect of the present disclosure is directed to a table tennis rubber sheet that is unlikely to lose hitting performance even after repeated hits, and at least one aspect of the present disclosure is directed to a table tennis racket that can maintain stable hitting performance for a long period of time. [Means for solving the problem]
[0007] According to at least one embodiment of the present disclosure, there is provided a table tennis rubber sheet having an elastomer sheet including a crosslinked silicone rubber, When the crosslinked silicone rubber is decomposed using trimethyl orthoformate, a decomposition product is obtained that contains at least a first component having a structure represented by the following formula (1) and a second component having a structure represented by the following formula (2): When the number of moles of the first component per 1 g of the elastic sheet is α mol and the number of moles of the second component per 1 g of the elastic sheet is β mol, α is 1.3×10 -5 ~1.0×10 -3 mol, β is 9.0×10 -6 mol or less, and A table tennis rubber sheet is provided in which α / (α+β) is 0.67 to 1.00: [ka] In formulas (1) and (2), R 1 are each independently an alkyl group having 1 to 10 carbon atoms; R 2each independently represents an alkylene group having 2 to 8 carbon atoms.
[0008] According to at least one aspect of the present disclosure, there is provided a table tennis racket comprising a racket body and a rubber sheet attached to at least one surface of the racket body, the rubber sheet being the table tennis rubber sheet described above. Effect of the Invention
[0009] According to at least one aspect of the present disclosure, it is possible to obtain a table tennis rubber sheet whose hitting performance is unlikely to deteriorate even with repeated hits. Also, according to at least one aspect of the present disclosure, it is possible to obtain a table tennis racket whose stable hitting performance can be maintained for a long period of time. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is an explanatory diagram of the behavior of a table tennis rubber sheet containing crosslinked silicone rubber with low α and high β when hitting a ball. [Diagram 2] FIG. 2 is an explanatory diagram of the behavior of the crosslinked silicone rubber when hitting a table tennis rubber sheet containing a crosslinked silicone rubber with a high α content and low β content according to the present disclosure. [Diagram 3] Schematic diagram of table tennis rubber sheet [Figure 4] Schematic diagram of a table tennis rubber sheet with multiple protrusions on the sponge sheet side [Diagram 5] Schematic diagram of a table tennis rubber sheet with multiple protrusions on the opposite side to the sponge sheet [Figure 6] Schematic diagram to explain the decomposition process of crosslinked silicone rubber [Figure 7] Schematic diagram of a mold used to make a flat solid rubber sheet [Figure 8] Schematic diagram of a mold for producing a solid rubber sheet with multiple protrusions [Figure 9] Schematic diagram for explaining the procedure for ball hitting performance evaluation DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In the present disclosure, the description of a numerical range such as "XX or more and YY or less" or "XX to YY" means a numerical range including the lower and upper limits, which are the endpoints, unless otherwise specified. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. In addition, in the present disclosure, for example, a description such as "at least one selected from the group consisting of XX, YY, and ZZ" means any of XX, YY, ZZ, a combination of XX and YY, a combination of XX and ZZ, a combination of YY and ZZ, or a combination of XX, YY, and ZZ.
[0012] As mentioned above, according to the study by the inventors, the silicone rubber rubber sheets described in Patent Document 1 and Patent Document 2 may have a lower ball speed as a hitting performance when repeatedly hit. Therefore, the inventors have further studied to obtain a table tennis rubber sheet that has stable hitting performance regardless of repeated hits. As a result, they have found that the table tennis rubber sheet having the following configuration contributes to achieving the above-mentioned object.
[0013] [composition] The elastic sheet includes a crosslinked silicone rubber. When the crosslinked silicone rubber is decomposed using trimethyl orthoformate, a decomposition product is obtained that contains at least a first component having a structure represented by the following formula (1) and a second component having a structure represented by the following formula (2): When the number of moles of the first component per 1 g of the elastic sheet is α mol and the number of moles of the second component per 1 g of the elastic sheet is β mol, α is 1.3×10 -5 ~1.0×10 -3 mol, β is 9.0×10 -6 mol or less, and Table tennis rubber sheet with α / (α+β) of 0.67 to 1.00: [ka] In formulas (1) and (2), R 1 are each independently an alkyl group having 1 to 10 carbon atoms; R 2 each independently represents an alkylene group having 2 to 8 carbon atoms.
[0014] The inventors speculate as follows as to why the table tennis rubber sheet having the above-mentioned configuration has stable ball hitting performance regardless of repeated hits.
[0015] When cross-linked silicone rubber is decomposed using trimethyl orthoformate, the parts that formed cross-linked structures by siloxane bonds are replaced with methoxy groups. Therefore, the first component having the structure shown in formula (1) contained in the decomposition product is considered to indicate the presence of a cross-linked structure in the cross-linked silicone rubber in which the molecular chain extends in four directions from the cross-linking point. The number of moles α (mol) of the first component per 1 g of elastomer sheet is the amount of cross-linked structures in which the molecular chain extends in four directions. Shows. The second component having the structure shown in formula (2) contained in the decomposition product is considered to represent the presence of a crosslinked structure in which the molecular chain extends in three directions from the crosslinking point in the crosslinked silicone rubber. The number of moles β (mol) of the second component per gram of elastomer sheet represents the amount of the crosslinked structure in which the molecular chain extends in three directions.
[0016] First, in Figs. 1A, 1B, and 1C, α is 1.3 × 10 -5 mol and β is 9.0×10 -6 This is a schematic diagram showing the behavior of cross-linked silicone rubber when a ball is hit with a table tennis rubber sheet having an elastomer sheet that contains cross-linked silicone rubber as a binder, the cross-linked silicone rubber having a molecular weight greater than 1.0 mol and an α / (α+β) ratio of less than 0.67.
[0017] FIG. 1A is a diagram showing the state before impact, with circles indicating cross-linking points 11 and molecular chains 12 extending in three directions from the cross-linking points. FIG. 1B is a diagram showing the state after impact, with arrows indicating the stress applied to cross-linking points 11 by the impact. This shows that stress dispersion is insufficient because molecular chains 12 extend in three directions from cross-linking points 11. FIG. 1C is a diagram showing the state after repeated impact, showing that insufficient stress dispersion has caused the cross-linking structure to change, resulting in variations in density at cross-linking points 11 and softening the elastomer sheet.
[0018] On the other hand, in Figs. 2A, 2B, and 2C, α was 1.3 × 10 -5 mol~1.0×10 -3 mol and β is 9.0×10 -6 mol or less and having an α / (α+β) ratio of 0.67 to 1.00, the elastic sheet containing the crosslinked silicone rubber as a binder.
[0019] FIG. 2A is a diagram showing the state before impact, in which circles indicate cross-linking points 21, and molecular chains 22 extend in four directions from the cross-linking points 21. 2B is a diagram showing the state when an impact is applied, with the arrows indicating the stress applied to the cross-linking point 21 by the impact. Since the molecular chains 22 extend in four directions from the cross-linking point, the stress is sufficiently dispersed. FIG. 2C shows the state after repeated impacts, and shows that sufficient stress dispersion results in little change in the cross-linked structure, suppressing softening of the elastic sheet.
[0020] In this way, cross-linked silicone rubber with a high α content and low β content can effectively distribute the stress at the cross-linking points caused by impact. As a result, it is thought that softening caused by repeated impacts can be suppressed, speed does not decrease, and stable hitting performance can be maintained. Preferred embodiments of the table tennis rubber sheet and the table tennis racket using the same will be described in detail below.
[0021] The table tennis rubber sheet has at least an elastomer sheet. The elastomer sheet contains crosslinked silicone rubber as a binder. In the elastomer sheet, the crosslinked silicone rubber can be used as a binder for, for example, pigments and inorganic fillers. By using the crosslinked silicone rubber, stable ball hitting performance can be achieved.
[0022] 3 is an example of a cross-sectional view in the thickness direction of a table tennis rubber sheet. This table tennis rubber sheet 3 is a rubber sheet in which a solid rubber sheet 31 and a sponge sheet 32 are laminated as elastic sheets. This table tennis rubber sheet 3 may be composed of only the solid rubber sheet 31. The elastic sheet in the table tennis rubber sheet may be the solid rubber sheet 31, the sponge sheet 32, or both the solid rubber sheet 31 and the sponge sheet 32. The elastic sheet is preferably the solid rubber sheet 31.
[0023] <Solid rubber sheet> Here, we will explain the material and shape constituting the solid rubber sheet 31 as an elastic sheet. First, we will explain the material constituting the solid rubber sheet 31. The solid rubber sheet 31 as an elastic sheet contains crosslinked silicone rubber from the viewpoints of excellent flexibility and deformation recovery, and small changes in temperature and over time.
[0024] The crosslinked silicone rubber may be, for example, a cured product of an addition-curing silicone rubber mixture, which contains, for example, an alkenyl-containing polyorganosiloxane, a hydrosilyl-containing polyorganosiloxane, and a hydrosilylation catalyst.
[0025] The alkenyl-group-containing polyorganosiloxane may, for example, be a compound represented by the following formula (3). [ka]
[0026] In formula (3), R 3 are each independently a methyl group or an alkenyl group, and at least two R 3 is an alkenyl group. Preferably, 500≦a≦50000. Examples of the alkenyl group include a vinyl group, an allyl group, a propenyl group, an isopropenyl group, a butenyl group, an isobutenyl group, a pentenyl group, and a hexenyl group, and preferably a is a vinyl group.
[0027] The alkenyl group-containing polyorganosiloxane is preferably at least one selected from the group consisting of compounds represented by the following formula (3-1) and compounds represented by the following formula (3-2). [ka]
[0028] In formula (3-1), R 3 are each independently an alkenyl group. Preferably, 500≦a1≦50000. Examples of the alkenyl group include a vinyl group, an allyl group, a propenyl group, an isopropenyl group, a butenyl group, an isobutenyl group, a pentenyl group, and a hexenyl group, and preferably a vinyl group.
[0029] In formula (3-2), R 3 are each independently an alkenyl group. Preferably, 1≦a3≦500, and 500≦a2+a3≦50000. Examples of the alkenyl group include a vinyl group, an allyl group, a propenyl group, an isopropenyl group, a butenyl group, an isobutenyl group, a pentenyl group, and a hexenyl group, and preferably a vinyl group. a, a1, and a2+a3 represent the average degree of polymerization. Each of a, a1, and a2+a3 is more preferably 1,000 to 10,000, and further preferably 2,000 to 5,000.
[0030] In the alkenyl group-containing polyorganosiloxane, The amount of trimethylsiloxy structure is preferably from 0.000 to 0.200 mol %, and more preferably from 0.000 to 0.070 mol %. The amount of the methylvinylsiloxane structure is preferably from 0.010 to 9,000 mol %, and more preferably from 0.050 to 1,100 mol %. The amount of the dimethylsiloxane structure is preferably from 90.000 to 99.900 mol %, and more preferably from 96.000 to 99.850 mol %. The amount of the dimethylvinylsiloxy structure is preferably from 0.000 to 0.200 mol %, and more preferably from 0.000 to 0.070 mol %.
[0031] An example of the hydrosilyl group-containing polyorganosiloxane is a compound represented by the following formula (4). [ka]
[0032] In formula (4), R 4 are each independently a methyl group or a hydrogen atom, and at least two R 4 is a hydrogen atom. Also, preferably, 5≦b≦1000. Preferably, R at both ends 4 is a methyl group. Crosslinked silicone rubber has, for example, a hydrosilyl group in the side chain.
[0033] The content of the hydrosilyl group-containing polyorganosiloxane in the addition curing type silicone rubber mixture is preferably such that the amount (molar ratio) of hydrosilyl groups in the hydrosilyl group-containing polyorganosiloxane is 1.1 to 20.0 times, more preferably 1.2 to 10.0 times, the amount of alkenyl groups in the alkenyl group-containing polyorganosiloxane.
[0034] Examples of the hydrosilylation catalyst include platinum-based, palladium-based, and rhodium-based catalysts, with platinum-based catalysts being particularly preferred. Examples of the platinum-based catalyst include chloroplatinic acid, an alcohol solution of chloroplatinic acid, a complex of chloroplatinic acid and an olefin, a complex of chloroplatinic acid and a vinylsiloxane, and platinum-supported silica.
[0035] The content of the hydrosilylation catalyst in the addition-curing silicone rubber mixture is preferably an amount such that the ratio of the mass of catalytic metal atoms to the mass of the alkenyl-group-containing polyorganosiloxane is in the range of 1 ppm or more and 100 ppm or less.
[0036] In addition, the cross-linked silicone rubber contained in the elastic sheet was decomposed with trimethyl orthoformate. When the decomposition product is decomposed, a decomposition product containing at least a first component having a structure represented by formula (1) and a second component having a structure represented by formula (2) is obtained. The number of moles of the obtained first component per 1 g of the elastomer sheet is defined as α mol, and the number of moles of the obtained second component per 1 g of the elastomer sheet is defined as β mol. In this case, α is 1.3×10 -5 ~1.0×10 -3 mol and β is 9.0×10 -6 mol or less.
[0037] [ka] In formulas (1) and (2), R 1 each independently represents an alkyl group having 1 to 10 carbon atoms (preferably having 1 to 4 carbon atoms, more preferably having 1 carbon atom); R 2 each independently represents an alkylene group having 2 to 8 carbon atoms (preferably 2 to 4 carbon atoms, more preferably 2 carbon atoms).
[0038] α is 1.3×10 -5 It is assumed that by having an α of 1.0×10 mol or more, the stress applied to the crosslinked silicone rubber during impact can be effectively dispersed, resulting in stable hitting performance. -3mol or less, the table tennis rubber sheet will have excellent hitting performance and stable hitting performance. -5 ~2.0×10 -4 mol, preferably 5.0×10 -5 ~1.5×10 -4 It is more preferable that it is mol.
[0039] In addition, β is 9.0×10 -6 By keeping β below 0.0×10 mol, there is little cross-linking structure in which the molecular chain extends in three directions, which reduces the effect of stress dispersion on the cross-linked silicone rubber during impact, resulting in stable hitting performance. -6 mol, preferably 0.0 to 5.0 × 10 -6 It is more preferable that it is mol.
[0040] And, α / (α+β) needs to be 0.67 to 1.00. With α / (α+β) of 0.67 to 1.00, it is presumed that the ratio of crosslinking points where the molecular chain extends in four directions is high, and the stress applied to the crosslinked silicone rubber during impact can be effectively dispersed, resulting in stable hitting performance. α / (α+β) is preferably 0.70 to 1.00, and more preferably 0.85 to 1.00.
[0041] In addition, the sum of α and β, α + β, is 1.4 × 10 -5 ~1.4×10 -4 mol. When crosslinked silicone rubber is decomposed with trimethyl orthoformate, α+β represents the sum of crosslinking points. By controlling it within the above range, it is possible to obtain a better table tennis rubber sheet. The ball hitting performance can be shown. α+β is preferably 1.7×10 -5 ~1.4×10 -4 mol.
[0042] In order to control the above α, there is a method of controlling the amount of crosslinking points from which the molecular chain extends in four directions. Such crosslinking points can be formed, for example, by the reaction of an alkenyl-containing polyorganosiloxane containing an alkenyl group at the side chain position with a hydrosilyl-containing polyorganosiloxane containing a hydrosilyl group at the side chain position. This reaction allows the molecular chain to extend in four directions from the crosslinking points.
[0043] In addition, in order to control β, there is a method of controlling the amount of crosslinking points where the molecular chain extends in three directions. Such crosslinking points can be formed, for example, by the reaction of an alkenyl-containing polyorganosiloxane containing an alkenyl group at the terminal position with a hydrosilyl-containing polyorganosiloxane containing a hydrosilyl group at the side chain position, or by the reaction of an alkenyl-containing polyorganosiloxane containing an alkenyl group at the side chain position with a hydrosilyl-containing polyorganosiloxane containing a hydrosilyl group at the terminal position. This reaction allows the molecular chain to extend in three directions from the crosslinking points.
[0044] In addition, the elastic sheet containing the crosslinked silicone rubber as a binder preferably contains a filler for the purpose of reinforcing effect. The filler is preferably an inorganic filler. The content of the inorganic filler in the elastic sheet is preferably 10.0 mass% or less based on the mass of the elastic sheet. By making the content 10.0 mass% or less, it is possible to suppress the inhibition of deformation recovery of the crosslinked silicone rubber caused by an excess of filler. In addition, the content of the filler is more preferably 8.0 mass% or less, and even more preferably 6.0 mass% or less. For example, the content of the inorganic filler is preferably 1.0 to 10.0 mass%, more preferably 2.0 to 8.0 mass%, and even more preferably 3.0 to 6.0 mass%.
[0045] Examples of inorganic fillers include zeolite, carbon black, silica, calcium carbonate, magnesium carbonate, kaolin, and talc. The filler is preferably at least one selected from the group consisting of carbon black and silica, and more preferably silica. Silica has a structure similar to that of crosslinked silicone rubber and is thought to act as a pseudo-crosslinking point, which is thought to suppress softening due to repeated impacts and provide excellent hitting performance. The number-average particle size of the primary particles of the filler is preferably 10 to 500 nm.
[0046] The content of the inorganic filler in the elastic sheet can be measured by the following procedure. Approximately 10 mg of a sample piece is taken from the elastic sheet, and its mass is weighed using a precision balance. This sample piece is placed on an alumina pan and inserted into a thermogravimetric analyzer. While recording the change in mass of the sample piece, the temperature is raised from 20°C to 600°C at a rate of 20°C / min in a nitrogen atmosphere, and then the sample is held at 600°C for 5 minutes. This causes all of the organic matter contained in the sample piece, such as silicone, to decompose and evaporate, leaving only the filler, allowing the mass of the filler contained in the sample piece to be calculated.
[0047] The elastic sheet is preferably a cured product of an addition-curing type silicone rubber mixture containing an alkenyl group-containing polyorganosiloxane, a hydrosilyl group-containing polyorganosiloxane, a hydrosilylation catalyst, and a filler. The elastic sheet may contain, in addition to the crosslinked silicone rubber as a binder, additives to the extent that the effects of the present disclosure are not impaired. The content of the crosslinked silicone rubber in the elastic sheet is preferably 80.0 to 99.0 mass %, more preferably 90.0 to 96.0 mass %. For example, a reaction regulator for adjusting the curing rate, a pigment for coloring, a plasticizer, a filler, an extender, and various other additives may be added to the addition-curing silicone rubber mixture as necessary.
[0048] <How to mix silicone rubber> Means for mixing the silicone rubber include the following means: For example, a dynamic mixer such as a single screw extruder, twin screw extruder, kneader mixer, two-roll mill, three-roll mill, Banbury mixer, continuous mixer, planetary mixer, or three-screw mixer, or a static mixer such as a static mixer, may be used.
[0049] <Evaluation of α content and β content in crosslinked silicone rubber> By reacting cross-linked silicone rubber with trimethyl orthoformate and methanol in the presence of sulfuric acid, the molecular chains of the cross-linked silicone rubber can be cut and decomposed into methoxysilane units. In this reaction, the siloxane bonds in the silicone rubber are cut, as shown in reaction formula 1 below. [ka] In the formula, R is an optional substituent.
[0050] The manner in which crosslinked silicone rubber is decomposed into methoxysilane units by this reaction will be explained using as an example a crosslinked silicone rubber having a partial structure as shown in Figure 6. In Figure 6, the siloxane bond in the crosslinked silicone rubber is cut at position 6 by the reaction shown in reaction formula 1, and as a result, it is decomposed into methoxysilane units as shown in the following formulas (5) to (8). [ka]
[0051] By analyzing the mixture of these methoxysilane units obtained by decomposition with GC / MS, each methoxysilane unit is detected as a different peak on the chromatogram. By determining the areas of these peaks, when crosslinked silicone rubber is decomposed using trimethyl orthoformate, a decomposition product containing a first component having a structure represented by formula (1) and a second component having a structure represented by formula (2) is obtained. Then, the number of moles of the obtained first component per 1 g of the elastomer sheet can be determined as α mol, and the number of moles of the obtained second component per 1 g of the elastomer sheet can be determined as β mol. Specific means will be described later.
[0052] Next, the shape of the solid rubber sheet 31 will be described. The solid rubber sheet 31 is flat, and is bonded to the sponge sheet 32 as shown in FIG. 3. The solid rubber sheet may have multiple protrusions. In that case, as shown in FIG. 4, the solid rubber sheet 41 in the table tennis rubber sheet 4 has multiple protrusions 43, and the tops of the protrusions 43 are bonded to the sponge sheet 42. Furthermore, as shown in FIG. 5, in the table tennis rubber sheet 5, the surface opposite to the protrusions 53 of the solid rubber 51 having multiple protrusions 53 may be bonded to the sponge sheet 52.
[0053] <How to mold solid rubber sheets> The method for forming the solid rubber sheet is not particularly limited, but one example is die molding using a heat press. In this molding method, molding is performed using a die 7 consisting of a lower die 71 and an upper die 72, as shown in Figure 7. During molding, a required amount of material is placed on the lower die 71, and the upper die 72 is placed on top of it, and the solid rubber sheet is formed by sufficiently heating and pressing with the heat press.
[0054] Furthermore, when forming protrusions on a solid rubber sheet, multiple recesses 83 may be provided in the lower die 81 of a mold 8 as shown in Fig. 8. The shape of the protrusions on a solid rubber sheet is regulated in "THE ITTF QUALITY PROGRAMME FOR RACKET COVERINGS-MANUAL" published by the International Table Tennis Federation, and it is preferable to determine the shape and arrangement of the recesses 83 so that the protrusion shape conforms to this regulation.
[0055] The thickness of the solid rubber sheet is also preferably in accordance with the above-mentioned regulations. For example, the thickness of the elastic sheet is preferably 0.3 to 2.0 mm, more preferably 1.0 to 2.0 mm. When protrusions are formed on the sheet, the thickness includes the protrusions. The total thickness of the table tennis rubber sheet is preferably 4.0 mm or less.
[0056] <Sponge sheet> The table tennis rubber sheet may be formed by laminating a sponge sheet on a solid rubber sheet. The material constituting the sponge sheet is not particularly limited, and known materials can be used. Examples include natural rubber, isoprene rubber, butadiene rubber, chloroprene rubber, butyl rubber, urethane rubber, and silicone rubber. Silicone rubber is preferable from the viewpoint of excellent flexibility and deformation recovery, and small temperature change and change over time. Examples of silicone rubber include a cured product obtained by foaming an addition-curing silicone rubber mixture. The thickness of the sponge sheet is not particularly limited, and may be within a known range. For example, it is preferable that it is within the range of the International Table Tennis Federation's regulations.
[0057] <Adhesion of solid rubber sheet and sponge sheet> The method of bonding the sponge sheet and the solid rubber sheet is not particularly limited, but examples include a method of applying an adhesive such as a modified silicone adhesive or a cyanoacrylate adhesive and bonding them together. Among these, a silicone adhesive is preferable because the adhesive layer has a moderate elasticity, so that cohesive failure is unlikely to occur in the adhesive layer when hitting the ball. In other words, the sponge sheet and the solid rubber sheet are preferably bonded with an adhesive, and more preferably with a silicone adhesive.
[0058] At least one embodiment of the present disclosure relates to a table tennis racket. The table tennis racket includes a racket body and a rubber sheet attached to at least one surface of the racket body, the rubber sheet being the table tennis rubber sheet described above. The table tennis rubber sheet may be made of an elastic sheet, and the elastic sheet may be a solid rubber sheet. Also, the table tennis rubber sheet may comprise the solid rubber sheet, which is the elastic sheet, and a sponge sheet, and the surface of the sponge sheet opposite to the surface facing the solid rubber sheet may be attached to the surface of the racket body.
[0059] The table tennis rubber sheet may be attached to both sides of the racket body. The method of adhering the table tennis rubber sheet to the racket body is not particularly limited, and any known method may be used. For example, a known adhesive for table tennis rackets may be used. In addition, the shape of the racket body may be There are no particular limitations on the type of the solvent, and any known solvent may be used. EXAMPLES
[0060] Below, several aspects of the present invention will be described in more detail with reference to specific examples of a table tennis rubber sheet and a table tennis racket.
[0061] Example 1 [Formation of solid rubber sheet] As siloxane 1, a vinyl group-containing polyorganosiloxane having an average degree of polymerization of 3,000 and consisting of 91.600 mol % dimethylsiloxane structure, 8.333 mol % methylvinylsiloxane structure, and 0.067 mol % dimethylvinylsiloxy structure was used. 200.0 g of siloxane 1, 0.1 g of platinum catalyst (product name: 3% Pt-VTS-VTS solution; manufactured by N.E. Chemcat Corporation), 0.1 g of reaction inhibitor (1-ethynyl-1-cyclohexanol; manufactured by Tokyo Chemical Industry Co., Ltd.), and 15.0 g of silica (product name: AEROSIL R976S; manufactured by Nippon Aerosil Co., Ltd.) were weighed out and added to a kneader mixer (product name: KH-1-S; manufactured by Inoue Seisakusho Co., Ltd.) and mixed uniformly to obtain a mixture.
[0062] To the resulting mixture, 66.7 g of hydrosilyl-containing polyorganosiloxane (trade name: HMS-501; manufactured by Gelest Inc.) was added, and the mixture was thoroughly mixed again using the kneader mixer to obtain a uniform mixture. The composition is shown in Table 1. Next, a required amount of the mixture was placed on the lower die 71 of the mold shown in Figure 7, and the upper die 72 was placed on top of it, and pressed for 10 minutes with a heat press machine (manufactured by Kansai Roll Co., Ltd.) with a hot plate heated to 120°C under a load of 10 MPa. The mold was then removed and cooled to room temperature, and the upper and lower dies were disassembled to remove the hardened solid rubber sheet. The solid rubber sheet had a thickness of 1.8 mm.
[0063] [α content and β content in elastic sheet (mol)] A 500 mg sample piece was cut out from the solid rubber sheet serving as the elastomer sheet, chopped into 5 mm squares, placed in a flask, and 245 mg of sulfuric acid was added, followed by heating at 60°C for 1 hour. After that, a mixture of 27.4 g of trimethyl orthoformate and 8.4 g of methanol was added to the flask and refluxed at 170°C for 8 hours to react, yielding a decomposition product of the crosslinked silicone rubber that constituted the elastomer sheet. The decomposition product was subjected to suction filtration to remove the filler, and the obtained filtrate was analyzed by GC / MS to determine α and β. The details of the GC / MS analysis are as follows. Equipment: GCMS QP2020 (product name, manufactured by Shimadzu Corporation) Sample injection volume: 1μL Injection temperature: 300℃ Split ratio: 1 / 50 Carrier gas: Helium Carrier gas flow rate: 1.3mL / min Column: Capillary column SH-1 Column temperature: Hold at 40°C for 1 minute, then increase at 7°C / min and hold at 299°C for 1 minute In the chromatogram obtained by GC / MS analysis, peaks corresponding to the four components of the above-mentioned formulas (5), (6), (7), and (8), which are decomposition products of crosslinked silicone rubber, were detected.
[0064] By calculating the area ratio of each of these peaks, the mass ratio of each component was calculated, and the following ratio was obtained. (5):(6):(7):(8) =3.2×10 -4 :1.4:2.1×10 -1 :1.8×10 -3 Each of these components (5), (6), (7), and (8) is present in the cross-linked silicone rubber before decomposition. These are components derived from the partial structures represented by the following formulas (5'), (6'), (7', and (8').
[0065] [ka]
[0066] From the molecular weights of the components of formulas (5), (6), (7), and (8) and the partial structures of formulas (5'), (6'), (7'), and (8'), the mass ratios of the partial structures of (5'), (6'), (7'), and (8') in the crosslinked silicone rubber before decomposition are calculated as follows: (5'):(6'):(7'):(8') =2.5×10 -4 :8.6×10 -1 :1.4×10-1 :1.2×10 -3
[0067] From this mass ratio, the mass of the partial structure (7') is 1.4 × 10 per 1 g of the elastic sheet. -1 g. The molecular weight of the partial structure (7') is 146, so the number of moles per gram is 9.6 × 10 -4 mol, and α is 9.6×10 -4 It is calculated in mol. The mass of the partial structure (8') is 1.2 x 10 per 1 g of crosslinked silicone rubber. -3 g and The molecular weight of the partial structure (8') is 153, so the number of moles per gram is 7.8 × 10 -6 mol, and β is 7.8×10 -6 It is calculated in mol. The calculations here were performed based on formulas (5'), (6'), (7'), and (8'). However, the amounts of the components in formulas (5), (6), (7), and (8) correspond 1:1 to the amounts of the structures in formulas (5'), (6'), (7'), and (8'), respectively, so the values of α and β ultimately become the same.
[0068] [Inorganic filler content] The inorganic filler content of the crosslinked silicone rubber constituting the solid rubber sheet, which is an elastic sheet, was measured by thermogravimetric analysis using the following procedure. A 10 mg sample piece was cut out from the solid rubber sheet. This sample piece was chopped into 1 mm squares, placed on an alumina pan, and weighed on a precision balance, and this mass was taken as the "mass before heating". This sample was placed in a thermogravimetric analyzer (product name: TGA / DSC3+; manufactured by Mettler Toledo). In a nitrogen atmosphere, the sample was heated from 20°C to 600°C at a heating rate of 20°C / min, and then held at 600°C for 5 minutes, thereby decomposing and volatilizing the organic matter contained in the sample, and a residue consisting of filler was obtained. The mass of this residue was measured and taken as the "mass after heating". The filler content was calculated from the values of the "mass before heating" and the "mass after heating" using the following (Equation 1). (Formula 1) "Filler content [mass%]" = ("Mass after heating [mg]" / "Mass before heating [mg]") x 100
[0069] [Attaching rubber sheets to table tennis rackets] A thin layer of adhesive for table tennis rackets (product name: Finezip; manufactured by Nippon Table Tennis Co., Ltd.) was applied to the solid rubber sheet and the blade of a table tennis racket (product name: Corbel; manufactured by Tamas Co., Ltd.). After drying at room temperature for about 30 minutes, the adhesive-coated surfaces of the solid rubber sheet and the blade were attached together and left at room temperature overnight to allow sufficient adhesion. After adhesion, the portion of the solid rubber sheet that protruded beyond the blade of the racket was cut off with scissors to obtain table tennis racket 1.
[0070] [Ball hitting performance evaluation] The ball hitting performance was evaluated at room temperature, 23°C, and 55% relative humidity. The procedure is explained with reference to Fig. 9. A table tennis racket 92 was attached to a metal plate 91, and the metal plate 91 was fixed at an angle of 45° to a horizontal stand 93. Furthermore, a ping-pong ball ejection port 94 of a table tennis robot (product name: YM-07; manufactured by Yasaka Co., Ltd.) was positioned 13 cm away from the center of the table tennis racket. A non-rotating ping-pong ball 95 was shot horizontally from a ping-pong ball ejection port 94 toward the center of a table tennis racket 92 at a ball speed of 8.6 m / s, and the ping-pong ball 95 hitting the table tennis racket 92 and bouncing off was photographed using a high-speed microscope (product name: VW-900; manufactured by Keyence Corporation) at a shutter speed of 1 / 8000 sec and a frame rate of 4000 fps.
[0071] From the obtained photographed images, 32 frames (elapsed time 0.008 seconds) were extracted before and after the ping-pong ball 95 hit the table tennis racket 92, and the speed of the ping-pong ball before and after it hit the table tennis racket was calculated from the distance the ping-pong ball moved during these 32 frames. (Formula 2) "Speed maintenance rate [%]" = ("Ball speed after hitting the table tennis racket [mm / sec]" / "Ball speed before hitting the table tennis racket [mm / sec]") x 100
[0072] The above evaluation was counted as one impact, and 100,000 impacts were repeated. The speed maintenance rate after the impact was calculated, and the speed change rate was calculated using the following formula 3 based on the speed maintenance rate of the first impact and the speed maintenance rate of the 100,000th impact. (Formula 3) "Speed change rate [%]" = ("100,000th speed maintenance rate" / "1st speed Retention rate”)×100
[0073] The ball-hitting performance was ranked based on the following criteria: Rank A: The speed change rate was 95.0% or more, demonstrating extremely excellent durability. Rank B: The speed change rate was 90.0% or more and less than 95.0%, demonstrating excellent durability. Rank C: The rate of change of speed was 85.0% or more and less than 90.0%, demonstrating sufficient durability. Rank D: The rate of change of speed was 80.0% or more and less than 85.0%, and sufficient durability was demonstrated. Rank E: The speed change rate was less than 80.0% and the vehicle did not demonstrate sufficient durability.
[0074] The results for table tennis racket 1 in Example 1 were that the speed maintenance rate after the first hit by the table tennis racket was 57.4%, and the speed maintenance rate after the 300,000th hit by the table tennis racket was 53.2%, so the speed change rate was 92.7%, and it was ranked B.
[0075] (Examples 2 to 16) Solid rubber sheets 2 to 16 were produced in the same manner as in Example 1, except that the vinyl group-containing polyorganosiloxane was changed to the siloxanes in Tables 1 and 2 below, and other materials used in the solid rubber sheets were changed as shown in Tables 3 and 4 below. Then, using the obtained solid rubber sheets 2 to 16, table tennis rackets 2 to 16 were produced in the same manner as in Example 1. Furthermore, the obtained table tennis rackets 2 to 16 were subjected to a hitting performance evaluation in the same manner as in Example 1. The results are shown in Tables 5 and 6.
[0076] [Table 1] In Tables 1 and 2, the numerical values for each structure, such as the dimethylsiloxane structure, indicate mole percent.
[0077] [Table 2]
[0078] [Table 3] In the table, for example, "9.6.E-04" means "9.6 x 10 -4 " indicates that.
[0079] [Table 4]
[0080] [Table 5]
[0081] [Table 6]
[0082] Comparative Example 1 100 parts by mass of natural rubber (product name: SVR-CV100; manufactured by DAU TIENG RUBBER CORP.), 50 parts by mass of plasticizer (product name: Pastel 2H-12; manufactured by Lion Specialty Chemicals Co., Ltd.), 30 parts by mass of magnesium carbonate (product name: Venus; manufactured by Kamishima Kogyo Co., Ltd.), 3 parts by mass of activated zinc oxide (product name: AZO; manufactured by Seido Co., Ltd.), and 3.5 parts by mass of zinc oxide (type 2; manufactured by Seido Chemical Co., Ltd.) were mixed and kneaded for 30 minutes at 60°C using a 7L kneader mixer to obtain a kneaded product containing no crosslinking agent.
[0083] Next, 6.5 parts by mass of sulfur (fine sulfur #200; manufactured by Hosoi Chemical Co., Ltd.), 1.3 parts by mass of a sulfenamide-based vulcanization accelerator (product name: Noccela CZ; manufactured by Ouchi Shinko Chemical Co., Ltd.), 0.75 parts by mass of a guanidine-based vulcanization accelerator (product name: Noccela D; manufactured by Ouchi Shinko Chemical Co., Ltd.), 0.5 parts by mass of a thiuram-based vulcanization accelerator (product name: Noccela TRA; manufactured by Ouchi Shinko Chemical Co., Ltd.), and 2 parts by mass of a vulcanization activator (product name: Knockmaster EGS; manufactured by Ouchi Shinko Chemical Co., Ltd.) were mixed with this kneaded material not containing a crosslinking agent, and the mixture was kneaded for 10 minutes at a temperature of 60°C using an 8-inch mixing roll to obtain a kneaded material for producing a solid rubber sheet.
[0084] The obtained kneaded material for producing a solid rubber sheet was subjected to the same operation as in Example 1, except that the heating temperature of the mold was changed to 160°C, to produce a solid rubber sheet 17. Thereafter, the solid rubber sheet 17 was attached to the blade of a table tennis racket "Korbel (manufactured by Tamas)" in the same manner as in Example 1 to produce a table tennis racket 17. Then, a hitting performance evaluation was carried out in the same manner as in Example 1. The results are shown in Table 8.
[0085] Comparative Example 2 A table tennis racket 18 was produced in the same manner as in Comparative Example 1, except that 100 parts by mass of natural rubber (product name: SVR-CV100; manufactured by DAU TIENG RUBBER CORP.) in Comparative Example 1 was changed to 85 parts by mass of "SVR-CV100" and 15 parts by mass of polybutadiene-based thermoplastic elastomer (product name: RB810; manufactured by JSR Corporation). Then, a hitting performance evaluation was carried out in the same manner as in Example 1. The results are shown in Table 8.
[0086] (Comparative Examples 3 to 5) Solid rubber sheets 19 to 21 were produced in the same manner as in Example 1, except that the materials used for the solid rubber sheets were changed as shown in Table 7 below. Then, using the obtained solid rubber sheets 19 to 21, table tennis rackets 19 to 21 were produced in the same manner as in Example 1. Furthermore, the obtained table tennis rackets 19 to 21 were subjected to a hitting performance evaluation in the same manner as in Example 1. The results are shown in Table 8.
[0087] [Table 7]
[0088] [Table 8]
[0089] In Examples 1 to 16, the ball hitting performance was ranked A to D. This is because α was 1.3×10 -5 ~1.0×10 -3 mol and β is 9.0×10 -6 It was presumed that this was because the elastic sheet was prevented from softening due to repeated impacts, since the elasticity of the elastic sheet was less than 1.00 mol and the ratio α / (α+β) was in the range of 0.67 to 1.00.
[0090] In addition, the α+β value of cross-linked silicone rubber is 1.4×10 -5 ~1.4×10 -4 The evaluation was better when the thickness was 1.0 mol. This was presumably because softening due to repeated blows was further suppressed.
[0091] Furthermore, when the inorganic filler content of the elastic sheet was 10.0 mass% or less, the evaluation was better. It was presumed that this was because the decrease in rubber elasticity of the crosslinked silicone rubber caused by an excess of filler was suppressed. Furthermore, when the inorganic filler was silica, the reinforcing effect on the crosslinked silicone rubber was high, and better hitting performance was obtained. When all of these conditions were satisfied, better hitting performance was obtained.
[0092] The hitting performance of Comparative Examples 1 and 2 was rated E. This was presumably because the elastic sheet did not contain silicone rubber, and softening of the elastic sheet in response to impact could not be suppressed.
[0093] Comparative Examples 3 to 5 were rated E in terms of hitting performance. -5 ~1.0×10 -3 mol, β is 9.0×10 -6It was presumed that this was because, for 0.5 to 1.00 mol or less, α / (α+β) did not satisfy any of the ranges of 0.67 to 1.00, and therefore the softening of the elastic sheet in response to impact could not be suppressed.
[0094] The present disclosure relates to the following configurations. (Configuration 1) A table tennis rubber sheet having an elastomer sheet containing crosslinked silicone rubber, When the crosslinked silicone rubber is decomposed using trimethyl orthoformate, a decomposition product is obtained that contains at least a first component having a structure represented by the following formula (1) and a second component having a structure represented by the following formula (2): When the number of moles of the first component per 1 g of the elastic sheet is α mol and the number of moles of the second component per 1 g of the elastic sheet is β mol, α is 1.3×10 -5 ~1.0×10 -3 mol, β is 9.0×10 -6 mol or less, and A table tennis rubber sheet characterized in that α / (α+β) is 0.67 to 1.00: TIFF2025017520000019.tif93168 In formulas (1) and (2), R 1 are each independently an alkyl group having 1 to 10 carbon atoms; R 2 each independently represents an alkylene group having 2 to 8 carbon atoms. (Configuration 2) The sum of the α and β, α + β, is 1.4 × 10 -5 ~1.4×10 -4 mol. The table tennis rubber sheet according to configuration 1. (Configuration 3) 3. The table tennis rubber sheet according to claim 1, wherein the elastic sheet contains 10.0% by mass or less of an inorganic filler based on the mass of the elastic sheet. (Configuration 4) The table tennis rubber sheet according to configuration 3, wherein the inorganic filler is silica. (Configuration 5) 5. The table tennis rubber sheet according to any one of configurations 1 to 4, wherein the crosslinked silicone rubber is a cured product of an addition curing type silicone rubber mixture. (Configuration 6) The table tennis rubber sheet according to configuration 5, wherein the addition curing type silicone rubber mixture contains an alkenyl group-containing polyorganosiloxane, a hydrosilyl group-containing polyorganosiloxane, and a hydrosilylation catalyst. (Configuration 7) 7. The table tennis rubber sheet according to any one of configurations 1 to 6, wherein the elastic sheet is a solid rubber sheet. (Configuration 8) A table tennis racket, The table tennis racket comprises a racket body and a rubber sheet attached to at least one surface of the racket body; A table tennis racket, comprising a rubber sheet as defined in any one of configurations 1 to 7. [Explanation of symbols]
[0095] 1, 2... cross-linked silicone rubber, 11, 12... cross-linking point, 12, 22... molecular chain, 3, 4, 5... table tennis rubber sheet, 31, 41, 51... solid rubber sheet, 32, 42, 52... sponge sheet, 43, 53... protrusion, 6. The position at which the siloxane bond is broken, 7, 8... mold, 71, 81... lower mold of the mold, 72, 82... upper mold of the mold, 83 dent, 91 metal plate, 92 table tennis racket, 93 table, 94 ping pong ball ejection hole, 95 ping pong ball
Claims
1. A table tennis rubber sheet having an elastomer sheet containing crosslinked silicone rubber, When the crosslinked silicone rubber is decomposed using trimethyl orthoformate, a decomposition product is obtained that contains at least a first component having a structure represented by the following formula (1) and a second component having a structure represented by the following formula (2): When the number of moles of the first component per 1 g of the elastic sheet is α mol and the number of moles of the second component per 1 g of the elastic sheet is β mol, α is 1.3 × 10 -5 ~1.0 x 10 -3 mol, β is 9.0 × 10 -6 mol or less, and A table tennis rubber sheet, characterized in that α / (α+β) is 0.67 to 1.00: In formulas (1) and (2), R 1 each independently represents an alkyl group having 1 to 10 carbon atoms; R 2 each independently represents an alkylene group having 2 to 8 carbon atoms.
2. The sum of α and β, α + β, is 1.4 × 10 -5 ~1.4 x 10 -4 mol. The table tennis rubber sheet according to claim 1.
3. The table tennis rubber sheet according to claim 1, wherein the elastic sheet contains 10.0 mass% or less of an inorganic filler based on the mass of the elastic sheet.
4. The table tennis rubber sheet according to claim 3, wherein the inorganic filler is silica.
5. The table tennis rubber sheet according to claim 1, wherein the crosslinked silicone rubber is a cured product of an addition curing type silicone rubber mixture.
6. The table tennis rubber sheet according to claim 5, wherein the addition curing type silicone rubber mixture contains an alkenyl group-containing polyorganosiloxane, a hydrosilyl group-containing polyorganosiloxane, and a hydrosilylation catalyst.
7. The table tennis rubber sheet according to claim 1, wherein the elastic sheet is a solid rubber sheet.
8. A table tennis racket, The table tennis racket comprises a racket body and a rubber sheet attached to at least one surface of the racket body; A table tennis racket, characterized in that the rubber sheet is the table tennis rubber sheet according to any one of claims 1 to 7.
Citation Information
Patent Citations
Rubber for table tennis and table tennis racket
JP2011056004A
Rubber for table tennis and table tennis racket
JP2011056005A